2021
DOI: 10.1021/acs.estlett.1c00432
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Strength and Species Drive Iron–Carbon Adsorption Dynamics: Implications for Carbon Cycling in Future Coastal Environments

Abstract: In coastal environments, sea level rise (SLR) will likely alter reactions between organic matter (OM) and iron (Fe) minerals. A molecular understanding of OM−Fe reactions in complex ionic matrices such as seawater is lacking. We investigated the temporal molecular composition and adsorption of coastal OM to ferrihydrite (Fh) over 24 h in low-ionic strength water (LIW) (I = 0.0009 M), midionic strength water (MIW) (I = 0.003 M) (freshwater proxy), and high-ionic strength water (HIW) (I = 0.6 M) (seawater proxy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…By intensity-normalized formula abundance, the initial DOM contained primarily unsaturated lignin/phenolic (60%) and N– aliphatic (20%) components, with smaller contributions of polyphenols (12%), N+ aliphatic (2%), polycyclic aromatics (5%), and carbohydrate-like (1%) contributions (Supporting Information Table S3 and Figure ). These compounds are typical in DOM. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…By intensity-normalized formula abundance, the initial DOM contained primarily unsaturated lignin/phenolic (60%) and N– aliphatic (20%) components, with smaller contributions of polyphenols (12%), N+ aliphatic (2%), polycyclic aromatics (5%), and carbohydrate-like (1%) contributions (Supporting Information Table S3 and Figure ). These compounds are typical in DOM. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Also relevant to climate change is sea-level rise and over-extraction of groundwater in coastal areas, which can result in seawater intrusion into aquifers, and can have the effect of altering groundwater ionic strength 28 . Changes to ionic strength can affect the ability of DOM to adsorb to mineral surfaces 29 31 . Furthermore, seawater intrusion can influence terminal electron acceptor availability and microbial composition of groundwater 32 , 33 which may result in changes to the metabolic pathways used to mineralise DOM and altered mineralisation rates 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The negative correlations between salinity, I Terr , and FDOM indicated that the terrigenous signatures were attenuated mainly through conservative mixing with seawater . In general, the effects of ionic strength on DOM composition (e.g., coagulation and subsequent precipitation) were expected to be negligible due to the narrow salinity range in this study (30.1–34.6). The average molecular mass, O/C ratios, and I DEG of DOM in bottom water increased from near- to offshore (Table S4), which is typical for the transition from land to ocean. , …”
Section: Discussionmentioning
confidence: 76%